Impact of radiation-induced soft error on embedded cryptography algorithms. (November 2021) - Bandeira, Vitor; Sampford, Jack; Garibotti, Rafael; Trindade, Matheus Garay; Bastos, Rodrigo Possamai; Reis, Ricardo; Ost, Luciano
Abstract: With the advance of autonomous systems, security is becoming the most crucial feature in different domains, highlighting the need for protection against potential attacks. Mitigation of these types of attacks can be achieved using embedded cryptography algorithms, which differ in performance, area, and reliability. This paper compares hardware implementations of the eXtended Tiny Encryption Algorithm (XTEA) and the Advanced Encryption Standard (AES) algorithms. Results show that the XTEA implementation gives the best relative performance (e.g., throughput, power), area, and soft error reliability trade-offs. Highlights: Cryptography solutions on FPGAs are susceptible to radiation-induced soft errors. XTEA presents a lower radiation sensitivity w.r.t. AES solutions. XTEA solution gives the best relative performance, area, and reliability trade-offs.